Analyzing telework, trustworthiness, and performance using leader-member exchange COVID-19 perspective - Brown, Michael A., Sr., 1956- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"Useful for people and organizations seeking answers to COVID-related issues of teleworking, this book a new look at teleworking, an examination of important factors, and a plan for improvement in the short and long term"--